Probiotic strains with hypocholesterolemic activity as potential basis of food supplement for prevention and concomitant treatment of cardiovascular diseases associated with high cholesterol level - Starovoitova, Svitlana; Spivak, Mykola (My University, 2024)
Globally, about 17 million people die from cardiovascular disease (CVD) every year, accounting for 31% of all deaths worldwide. High serum cholesterol is regarded by many as the main cause of coronary atherosclerosis, and it has been well established that elevated cholesterol is associated with an increased risk of CVD. Apart from modulating the gut functionality, probiotics have also been associated with various other health benefits such as brain functioning, boosting immunity, reducing cholesterol, and promoting metabolic homeostasis through their biological mechanisms in the body. Several mechanisms of involvement of the microbiome in maintaining lipid metabolism at a physiological level and preventing the development of hypercholesterolemia are assumed: deconjugation of bile acids and reduction of their resorption due to the synthesis of specialized hydrolases; incorporation of cholesterol into the lipid layer of the cell membrane; transformation of cholesterol into coprostanol and its removal from the body together with feces; inhibition of cholesterol synthesis in the liver.

Щороку в усьому світі близько 17 мільйонів людей помирають від серцево-судинних захворювань (ССЗ), що становить 31% усіх смертей у світі. Багато хто вважає високий рівень холестерину в сироватці головною причиною коронарного атеросклерозу, і було точно встановлено, що підвищений рівень холестерину пов’язаний із підвищеним ризиком ССЗ. Окрім модуляції функціональності кишечника, пробіотики також пов’язані з різними іншими перевагами для здоров’я, такими як функціонування мозку, підвищення імунітету, зниження рівня холестерину та сприяння метаболічному гомеостазу через їхні біологічні механізми в організмі. Передбачено кілька механізмів участі мікробіому в підтримці ліпідного обміну на фізіологічному рівні та запобіганні розвитку гіперхолестеринемії: декон’югація жовчних кислот і зниження їх резорбції за рахунок синтезу спеціалізованих гідролаз; вбудовування холестерину в ліпідний шар клітинної мембрани; перетворення холестерину в копростанол і виведення його з організму разом з калом; пригнічення синтезу холестерину в печінці.
Keywords: probiotic strains; hypocholesterolemic activity; food supplement; cardiovascular diseases; пробіотичні штами; гіпохолестеринемічна активність; функціональні продукти харчування; серцево-судинні захворювання; кафедра біотехнології і мікробіології